Piezo-resistive characteristics of graphene-based cement materials - Rehman, S.K.U.; Ibrahim, Z.; Javed, M.F.; Hanif, M.U. (2017)
iezo-resistive characteristics of cement-based materials were investigated using gra-phene nanoplatelets (GNPs). These phenomena provide composite materials with the ca-pability to sense their own strain. In this study, very small amount of GNP (i.e., 0.03% by weight of cement) was used. Results show that compressive strength and strain capability are enhanced by 30% and 80%, respectively, after the addition of GNPs. Electrical resis-tivity values are decreased by 42% for GNP–cement composite. The fractional change in resistivity confirms that the sensitivity of the GNP–cement composite increases with com-pressive loading. Therefore, GNP-based cement composites can be an appropriate choice for self-sensing purposes.